Cognitive impairment and depression symptoms are independently associated with suicidal ideation in US Veterans. (April 2020) - Ryan, Arthur T.; Phalen, Peter; Jahn, Danielle R.; Wastler, Heather; Bennett, Melanie; Ghahramanlou-Holloway, Marjan; Schwartz, Barbara
Highlights: Memory, attention, and total cognition are associated with the severity of suicidal ideation, but do not predict its prescence or abscence. Depression symptoms predict both the severity and presence or absence of suicidal ideation. Cognitive indicies remain associated with suicidal ideation severity when depression symptoms are controlled for. Abstract: Depression is associated with cognitive impairment and suicidality. The independent association between cognitive impairment and suicidality is less clear. We examined the relationship between suicidal ideation and cognitive impairment in a sample of 50 veterans with depressive disorder diagnoses. Using zero-inflated Poisson regression, the severity of suicidal ideation was negatively associated with attention (incidence rate ratio [IRR] = 0.78, p  < .001), memory (IRR = 0.87, p  < .001), and total cognition (IRR = 0.90, p  = .007) index scores as measured by the Dementia Rating Scale 2 (DRS-2). These three indices continued to significantly predict suicidal ideation severity once depression symptoms were controlled for.